Aqidah Tauhid sebagai Dasar Pendidikan Anak dalam Perspektif Al Qur’an - Nurachman, Azhar; Ikhsanuddin, Muhammad; Kurniyadi, Mahmud Darul; Hasan, Ismail; Baidan, Nashruddin (Lembaga Yasin AlSys, 2024)
The concept of monotheistic faith (aqidah tauhid) is the fundamental basis of belief that must be correct for a Muslim. Therefore, a correct understanding of aqidah is something that must be instilled in the education process of a child. The correct concept of aqidah tauhid, when used in the education process, will give rise to strong morals and character. Thus, this article will elaborate on the correct concept of aqidah tauhid, its importance as the foundation of education, and the application of tauhid in the Qur'an and its implementation in child education. We observe that the current generation is far from being characterized as morally superior individuals, and this is because the foundation of tauhid in education is not functioning well. Therefore, this article will attempt to rectify the basic concept of education with a proper understanding of Aqidah.